Analisis Sifat Mekanik Uji Tarik Material Komposit Serat Karbon–Epoksi 1011l dengan Metode Manufaktur yang Berbeda - Utama, Agus Bayu; Abdurohman, Kosim; Habibullah, Moh.; Agustian, Rialdi (Universitas Muhammadiyah Metro, 2026)
Carbon fiber reinforced polymer composites are widely used in structural applications due to their high strength-to-weight ratio. Manufacturing methods significantly affect fiber impregnation quality, void content, and mechanical properties. This study investigates the effect of different manufacturing methods on the tensile properties of carbon fiber–epoxy 1011L composites with 0° fiber orientation. Three manufacturing methods were used: hand lay-up (HLU), vacuum bagging (VB), and vacuum assisted resin infusion (VARI). A total of 21 specimens were tested using a Universal Testing Machine (UTM) at the National Research and Innovation Agency (BRIN) following ASTM D3039. The results show that The VARI method showed the best mechanical performance with an average maximum point stress (MPS) of 774,31 MPa and an elastic modulus (ME) of 39.313 MPa, followed by the vacuum bagging and hand lay-up methods. The hand lay-up method produced the lowest MPS and ME values, at 507,72 MPa and 20.401 MPa, respectively. The VARI method produces the best mechanical properties compared to the hand lay-up and vacuum bagging methods.